Formally testing the protocol performances. (2015) - Che, Xiaoping; Maag, Stephane
The validation of systems and specifically the conformance testing of communicating protocols is a crucial step to their development. Many approaches have been developed for a while, among which, the formal ones have proved their efficiency to test these protocols. These approaches are divided in two main sets: active and passive testing techniques. While they both have their own advantages and drawbacks, passive testing techniques are the only ones that can be applied when the controllability of the system interfaces is unavailable or when the implementation under test cannot be stimulated in runtime. In this paper, we present a logicbased passive testing approach to test in a formal way the conformance and the protocol performance requirements provided by the protocol standard or experts. We aim at formally specifying time related protocol properties in order to check them on real execution traces. Based on a new algorithm, a prototype is here developed and experienced. In order to evaluate and assess our technique, we present experiments through a set of IMS/SIP properties (regarding the conformance and the protocol performance) and execution traces. We finally discuss the results by providing relevant verdicts.